Clinical Characteristics and Visual Outcomes in Patients with Intralenticular Foreign Bodies with Self-Sealing Corneal Penetrating Wounds. (22nd June 2021) - Su, Zhitao; Wang, Yuanqi; Yi, Quanyong; Lin, Lin; Lai, Kairan; Ye, Panpan; Wang, Yao; Fang, Xiaoyun
Abstract : Purpose . Siderosis bulbi may occur as a result of retained intralenticular foreign bodies (ILFBs) that were missed during examination in patients with self-sealing wounds and without a significant decrease in visual acuity. This study aimed to explore the clinical characteristics and visual outcomes of ILFBs with self-sealing corneal penetrating wounds. Methods . Fifteen eyes of 15 patients with ILFBs and self-sealing corneal penetrating wounds, seen between October 2014 and September 2019, were retrospectively analyzed. Data regarding the patient demographics, clinical features, surgical procedure, and initial and final best-corrected visual acuity (BCVA) were analyzed. Results . All patients were male with a mean age of 41 years. The foreign bodies passed through the cornea, sometimes through the iris, through the anterior capsule, and finally localized in the lens. All ILFBs were pointed and metallic objects and were successfully removed with phacoemulsification and posterior chamber intraocular lens (IOL) implantation. Anterior capsule violation was found in three eyes, but no posterior capsule rupture was found. The IOL was placed in a capsule bag in all the cases. The BCVA ranged from 20/200 to 20/25 preoperatively and improved to between 20/32 and 20/20 at the last follow-up visit. The IOLs were well-centered. Apart from posterior capsule opacity in four eyes, no other postoperative complications were found. Conclusions . In patients with a pointed metallic ILFB and self-sealing corneal penetrating wounds (with or without cataracts), early diagnosis and removal of the metallic ILFB combined with lens removal and IOL implantation may avoid late complications and achieve good visual outcomes.